Pneumothoraces in collagen VI-related dystrophy: a case series and recommendations for management. Issue 2 (23rd June 2017) - Fraser, Kristin L.; Wong, Scott; Foley, A. Reghan; Chhibber, Sameer; Bönnemann, Carsten G.; Lesser, Daniel J.; Grosmann, Carla; Rutkowski, Anne
Collagen VI-related dystrophy (collagen VI-RD) is a rare neuromuscular condition caused by mutations in the COL6A1, COL6A2 or COL6A3 genes. The phenotypic spectrum includes early-onset Ullrich congenital muscular dystrophy, adult-onset Bethlem myopathy and an intermediate phenotype. The disorder is characterised by distal hyperlaxity and progressive muscle weakness, joint contractures and respiratory insufficiency. Respiratory insufficiency is attributed to chest wall contractures, scoliosis, impaired diaphragmatic function and intercostal muscle weakness. To date, intrinsic parenchymal lung disease has not been implicated in the inevitable respiratory decline of these patients. This series focuses on pneumothorax, an important but previously under-recognised disease manifestation of collagen VI-RD. We describe two distinct clinical presentations within collagen VI-RD patients with pneumothorax. The first cohort consists of neonates and children with a single pneumothorax in the setting of large intrathoracic pressure changes. The second group is made up of adult patients with recurrent pneumothoraces, associated with chest computed tomography scan evidence of parenchymal lung disease. We describe treatment challenges in this unique population with respect to expectant observation, tube thoracostomy and open pleurodesis. Based on this experience, we offer recommendations for early identification of lung disease in collagen VI-RD and definitive intervention. Collagen VI-RD patients may experience unprovoked or recurrent pneumothorax from parenchymal lung changes http://ow.ly/ZL3h30ce0Bk